Analysis of the conceptions and expectations of students in the courses of Pedagogy, Administration and Human Resources about the discipline of Science, Technology and Society - Souza, Alexandre (2012)
Provided for the education curricula since 1960, the focus on Science, Technology and Society (STS) has been poorly implemented even until today. Set as a goal to be achieved at all levels of education by 2014, in Brazil it is necessary to undertake specific actions in pursuit of putting into practice what has been stalled over the years in Education. As a result of joint efforts of teachers and students of the Masters in Teaching Science and Mathematics at the Universidade Cruzeiro do Sul comes the challenge of providing a specific discipline dealing with the concepts of STS, offered as a optional special, initially for students of Pedagogy and later, due to the interest of some students, for the course of Administration and Human Resources of this institution. The survey of previous conceptions of students enrolled in the Special Discipline Elective Science, Technology and Society (CTS DOP) on the triad of STS showed a great ignorance on the same theme. The reports reveal conceptions of students who approach the linear model of development. As to the generated expectations in terms of discipline, there stand out the desires of expansion of knowledge for possible applications in personal and professional life. This research aims to evaluate the current course, while identifying ways to improve and strengthen the STS movement in education.